1993
DOI: 10.1111/j.1471-4159.1993.tb03180.x
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic α2 Adrenoceptors Inhibit Glutamate Release from Rat Spinal Cord Synaptosomes

Abstract: Abstract:The presynaptic regulation of amino acid release from nerve terminals was investigated using synaptosomes prepared from the rat spinal cord. The basal releases of endogenous glutamate (Glu), aspartate (Asp), and y-aminobutyric acid (GABA) were 34.6, 21.5, and 10.0 pmol/min/ mg of protein, respectively. Exposure to a depolarizing concentration of KCl (30 mkI) evoked 2.7-, 1 . 5 , and 2.9-fold increases in Glu, Asp, and GABA release, respectively. Clonidine reduced the K+-evoked overflow of Glu to 56% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 25 publications
2
33
1
1
Order By: Relevance
“…For example, glutamatergic excitatory postsynaptic potentials (EPSCs) in dorsal motor vagal neurons (6), sympathetic preganglionic neurons (42), dorsal horn neurons (46), and cultured hippocampal neurons are inhibited by activation of presynaptic ␣ 2 -receptors. Clonidine also reduces the amount of glutamate that is released spontaneously from spinal synaptosomes (28) and from slices in response to capsaicin (66).…”
Section: Discussionmentioning
confidence: 99%
“…For example, glutamatergic excitatory postsynaptic potentials (EPSCs) in dorsal motor vagal neurons (6), sympathetic preganglionic neurons (42), dorsal horn neurons (46), and cultured hippocampal neurons are inhibited by activation of presynaptic ␣ 2 -receptors. Clonidine also reduces the amount of glutamate that is released spontaneously from spinal synaptosomes (28) and from slices in response to capsaicin (66).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of α 2 -adrenoceptors increases potassium conductance in dorsal horn neurons, which produces hyperpolarization and decreases excitability, thereby contributing to analgesia (North and Yoshimura, 1984;Ocana and Baeyens, 1993;Grudt et al, 1995). On the other hand, α 2 -adrenoceptor agonists reduce the stimulus-evoked release of substance P (Kuraishi et al, 1985;Pang and Vasko, 1986) and glutamate (Kamisaki et al, 1993;Ueda et al, 1995) in the spinal cord, thus suppressing nociceptive transmission. The locus ceruleus in the brainstem is a major cell group of catecholaminergic neurons and is known to project to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies in DRG cell cultures and isolated spinal cord synaptosomes have demonstrated α2-AR agonist-mediated inhibition of stimulus-evoked SP, calcitonin gene-related peptide or glutamate release. [62][63][64] Supporting studies showing that mRNA encodes the α2A and α2C-ARs in DRG neurons after peripheral nerve injury or paw inflammation, 65,66 and another study using in vivo patch-clamp recording revealed that NE inhibited the barrage of excitatory postsynaptic potentials in rat spinal cord neurons initiated by nociceptive stimuli applied to the hindlimb. 65 Thus, the activation of α2-ARs and subsequent inhibition of primary afferent terminals is highly likely to play an important role in α2-ARs-mediated antinociception.…”
Section: Discussionmentioning
confidence: 82%